Biochemical parameters and adaptation of white rats with active and passive type of behavior under immobilization stress - Fedorenko Yu.V. (Medičnì Perspektivi)
The aim was to study dynamics of changes of certain biochemical indices and the development of adaptation in white rats with active and passive type of behavior under the influence of immobilization stress. Experiments were conducted on white rats, previously divided into groups of active and passive ones, on the basis of indicators of activity in the test “open field”. Modeling of immobilization stress was carried out by placing the animals in plastic boxes for 6 hours daily within 30 days. It was found that the immobilization caused changes of carbohydrate, lipid, calcium metabolism, activity of alkaline phosphatase, alanine- and aspartataminotransferase in blood serum of both experimental groups. However, the intensity, direction of the biochemical parameters, development in time depends on the type of animal behavior. To a greater degree active animals reacted to immobilization by changing of concentration of glucose and calcium in the blood on the 3rd and 5th day of the experiment, changes of all investigated parameters were observed on the 10th and 30th day of the experiment. Animals with active type of behavior appeared to be more susceptible to stress mobilization, but the intensity of their metabolic processes was higher than in animals with a passive type of behavior. This is testified by the highest level of blood glucose and lower levels of total cholesterol and triglycerides, as well as more active processes of calcium metabolism in the active animals than passive ones. Thus, dynamics of changes of biochemical parameters and the proceeding of the adaptation process in the conditions of immobilization stress depends on individually-typological features of animal behavior. This indicates to the necessity of differentiated approach to correction of adaptation disorders due to the action of immobilization stress on the organism with different typology of behavior.